Maternal and perinatal mortality in Municipalities and Townships of the Land Border. Colombia 1998 - 2016 - Ríos, Erika (2022)
Abstract: Maternal and perinatal mortality is a priority public health issue that is particularly difficult to control in border areas. Objectives: To describe the behavior of maternal and perinatal mortality in the border territories of Colombia, between 1998 and 2016; and to establish its association with sociodemographic, geographic and health care factors. Methods: Retrospective observational study, based on official records. Maternal mortality ratio (MMR) and perinatal mortality ratio (RMP) were calculated for the period 1998-2016, identifying inflection points through Joinpoint analysis. Likewise, bivariate and multivariate analyses were performed. Results: From 54 municipalities and 12 borders townships belonging to 12 Departments, 687 records maternal mortality records and 12,786 perinatal mortality records were obtained. The ratios observed were 88 x 100,000 BA for MMR and 16 x 1,000 NV for PMR. The trend of these types of mortality was downward. The highest values of perinatal mortality were significantly associated with maternal age 35-54 years, care by subsidized regime, low educational level, women without a partner, and multiple pregnancies. Conclusion: Maternal and perinatal mortality registered in border municipalities is above the national average.